New SMA Actuator with High Energy Efficiency and Quick Response - Jee, K. K.; Han, J. H.; Park, J. M.; Jang, W. Y. (PRICM 7, PTS 1-3, 2010)
The main drawbacks of SMA actuators are a slow response and a waste of electric power. The power should be continuously supplied for SMA elements to remain in the austenite state until the actuator begins to move to the other position. The problems are more serious when batteries and thick SMA elements are used. We develop a new SMA actuator which consumes little energy and responds very quickly. The actuator consists of a specially designed bias spring structure, and two SMA elements which exert the force in opposite direction to each other. The bias spring, unlike a common spring which has one stable position, has two stable positions. A SMA 1, for instance, contracts on heating by electricity, the actuator takes one stable configuration. No further power supply is necessary to maintain the stable position, providing enough time for the SMA1 to cool. When the other SMA2 is heated, it contracts with enough force to move the bias spring and to expand the already-cooled SMA1. Power supply stops immediately after the actuator takes the other stable configuration, causing power saving and quick response.